My Lai : Vietnam, 1968, and the descent into darkness - Jones, Howard, 1940- (Pivotal moments in American history., 2017)
"In this raw, searing new narrative account, Howard Jones reopens the case of My Lai by examining individual accounts of both victims and soldiers through extensive archival and original research. Jones evokes the horror of the event itself, the attempt to suppress it, as well as the response to Calley's sentence and the seemingly unanswerable question of whether he had merely been following orders. My Lai also surveys how news of the slaughter intensified opposition to the Vietnam War by undermining any pretense of American moral superiority. Compelling, comprehensive, and sobering, Howard Jones' My Lai chronicles how the strategic failures and competing objectives of American leaders resulted in one of the most devastating tragedies of the Vietnam War"--